2013
DOI: 10.5935/0103-507x.20130041
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare associated infections caused by coagulase-negativeStaphylococciin a neonatal intensive care unit

Abstract: ObjectiveThis study sought to evaluate infections related to health care caused by coagulase-negative Staphylococci in a neonatal intensive care unit by assessing antimicrobial susceptibility profiles and potentially effective antibiotic regimens. MethodsThis was a retrospective descriptive study performed on a case series of healthcare-associated infections, and the antimicrobial susceptibility profiles were evaluated. Newborns from other hospitals who were admitted to a neonatal intensive care unit in Rio de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Of a total of 5596 citations identified, 138 met the criteria for abstract review and 52 met the criteria for full-text assessment, of which 15 met the inclusion criteria for this review, namely, Kawagoe, JY et al 2001 [ 16 ]; Nagata, E et al 2002 [ 17 ]; Pessoa-Silva, CL et al 2004 [ 18 ]; Couto, RC et al 2007 [ 19 ]; Távora, AC et al 2008 [ 20 ]; Pereira, SM et al 2009 [ 21 ]; Catarino, CF et al 2012 [ 22 ]; Dal-Bó, K et al 2012 [ 23 ]; Freitas, BA et al 2012 [ 24 ]; Ventura, CM et al 2012 [ 25 ]; Romanelli, RM et al 2013 [ 26 ]; da Silva, AR et al 2013 [ 27 ]; de Souza Rugolo, LM et al 2014 [ 28 ]; Urzedo, JE et al 2014 [ 29 ]; Freitas, FTM et al 2019 [ 30 ] (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of a total of 5596 citations identified, 138 met the criteria for abstract review and 52 met the criteria for full-text assessment, of which 15 met the inclusion criteria for this review, namely, Kawagoe, JY et al 2001 [ 16 ]; Nagata, E et al 2002 [ 17 ]; Pessoa-Silva, CL et al 2004 [ 18 ]; Couto, RC et al 2007 [ 19 ]; Távora, AC et al 2008 [ 20 ]; Pereira, SM et al 2009 [ 21 ]; Catarino, CF et al 2012 [ 22 ]; Dal-Bó, K et al 2012 [ 23 ]; Freitas, BA et al 2012 [ 24 ]; Ventura, CM et al 2012 [ 25 ]; Romanelli, RM et al 2013 [ 26 ]; da Silva, AR et al 2013 [ 27 ]; de Souza Rugolo, LM et al 2014 [ 28 ]; Urzedo, JE et al 2014 [ 29 ]; Freitas, FTM et al 2019 [ 30 ] (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies (80.0%) included all infants admitted to the NICU, two (13.3%) included only infants < 1500 g, and one (6.7%) included only preterm infants. According to the definition of HAI, seven (46.7%) studies reported the use of the American Centers for Disease Control and Prevention (CDC) [ 27 ], four (26.6%) reported the use of the Brazilian Sanitary Agency (ANVISA) [ 28 ], two (13.3%) did not report which definition they used, one (6.7%) reported the use of both CDC and ANVISA definitions, and one (6.7%) developed its own definition. Table 1 shows a summary of the characteristics of the assessed studies.…”
Section: Resultsmentioning
confidence: 99%
“…Studies from some European countries [ 23 ] and Brazil [ 24 ] have documented the contributions of CoNS in neonatal sepsis, which could result in increased risk of mortality and morbidities., There are limited data on the incidence of CoNS in neonatal sepsis in Kuwait [ 25 , 26 ]. However, there are no studies on the molecular characteristics of CoNS associated with neonatal sepsis in Kuwait.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CoNS are usually saprophytic bacteria in a patient's microbiota; thus, they do not have a high antibiotic resistance that explains the minor differences observed in the MAR between the wards. The lower MAR of SA in the medical wards compared with the ICU can be explained by the lower exposure to antibiotics, and the low MAR of CoNS in the paediatric wards is easily explained by the overall low exposure time of children to antibiotics, due to the low age ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%